2022
DOI: 10.3389/fnut.2022.993334
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive lipidomics analysis reveals the changes in lipid profile of camellia oil affected by insect damage

Abstract: Information on changes in lipid composition of seed oils under biotic stresses is scare. The camellia weevil, Curculio chinensis (Coleoptera: Curculionidae) as a notorious seed predator of Camellia species, has caused huge economic losses in China. Lipidomics is used in this study to reveal the lipid composition of camellia oil and its changes after insect damage. 278 lipids including glycerolipids (GL) (221), glycerophospholipids (GP) (34), fatty acyls (FA) (13), sphingolipids (SP) (8), prenol lipids (PR) (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…This method may also be used to study the lipid changes that occur in pecans during storage [1,10]. However, there has been minimal success in characterizing the lipid composition in edible vegetable oil utilizing lipidomic analysis [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This method may also be used to study the lipid changes that occur in pecans during storage [1,10]. However, there has been minimal success in characterizing the lipid composition in edible vegetable oil utilizing lipidomic analysis [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Insect infestations can have a major impact on the quality and productivity of pecan crops, resulting in financial losses for growers [17]. Because of the possible consequences for nutritional quality, flavor, shelf life, and overall pest resistance, the influence of insect stress on the lipid metabolism and composition of oilseeds has received increased attention [16]. It has been shown that biotic pressures such as insect pests affect the fatty acid composition and several other quality components of oilseeds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 The advantages of lipidomics in the analysis of degraded vegetable oils and animal fats are: (1) lipidomics is not the analysis of individual lipids, but the simultaneous study of whole lipids, analyzing vegetable oils and animal fats from a systematic perspective; [11][12][13] (2) lipidomics has led us to identify new signaling molecules, discover potential biomarkers for differences in vegetable oils and animal fats, and provide effective assistance for the distinction and traceability of vegetable oils and animal fats. [14][15][16] The innovation points of this study include: (1) compared with previous studies, this paper analyzes more types and quantities of samples and dynamically monitors the changes in the lipid composition and content of 13 different types of vegetable oils and animal fats during aging on ve different carriers; (2) solves the problem of difficult identication of aged vegetable oils and animal fats in forensic science. This paper simulates the changes in the lipid composition and content of vegetable oils and animal fats during aging on ve different carriers under extremely hot conditions.…”
Section: Introductionmentioning
confidence: 99%
“…10 The advantages of lipidomics in the analysis of degraded vegetable oils and animal fats are: (1) lipidomics is not the analysis of individual lipids, but the simultaneous study of whole lipids, analyzing vegetable oils and animal fats from a systematic perspective; 11–13 (2) lipidomics has led us to identify new signaling molecules, discover potential biomarkers for differences in vegetable oils and animal fats, and provide effective assistance for the distinction and traceability of vegetable oils and animal fats. 14–16…”
Section: Introductionmentioning
confidence: 99%